The ESP Technology-Supported Learning Environment - Živković, Slađana (European Journal of Social Science Education and Research, 2016)
This paper discusses the implementation of computers and the Internet technology in the learning environment within the ESP context. Designing and implementing digital technology in the teaching and learning process is one of the most demanding tasks. The use of technologies in the ESP classroom enables students to be active and collaborative, which contributes to improving learning achievements and increasing learning outcomes. The ultimate goal is to improve the quality of learning experiences, as well as to produce a highly social and authentic, supportive and productive learning environment that allows students the construction of relevant knowledge. The study examines students’ perceptions towards the implementation of digital technologies in the classroom. The results of the research show that students have very positive attitudes towards computers and the Internet technologies and their integration in the ESP learning environment.